A randomized controlled trial of generic and localized MedlinePlus-based information resources for hard-to-reach urban Hispanic community. (9th November 2022) - Zhang, Tianmai M; Millery, Mari; Aguirre, Alejandra N; Kukafka, Rita
Abstract: Objective: To determine if the Conexion digital localized health information resource about diabetes and depression could increase patient activation among Hispanic low-income adults. Materials and Methods: A nonblinded randomized controlled trial was conducted (NCT03984929). Participants at least 18 years old living in Washington Heights/Inwood, New York, were recruited from the community between July 2019 and August 2020 and randomized 1:1 to either the intervention group (localization of MedlinePlus resources customized with community components) or the control group (no localized community components). The primary outcome, patient activation, and secondary outcomes, knowledge, self-efficacy, and behavior change, were collected through surveys at 1-month follow-up. Results: Of the 134 participants recruited, 50.7% ( n  = 68) completed the 1-month follow-up. We found no statistically significant differences in the sociodemographic and baseline characteristics between those who missed the 1-month survey and those who completed it. No significant differences were observed in patient activation at 1-month. However, patient activation among all participants ( n  = 68) significantly increased ( P  =   .048). Statistically significant improvements were also found in self-efficacy ( P  <   .03). In multivariate analysis, birth country outside the United States and higher self-rated attachment to the community emerged as significant predictors of higher patient activation scores. Discussion: While the trial did not detect significant differences between groups, all participants demonstrated increased patient activation scores and improved secondary outcomes. While other factors may have contributed to this increase, our study suggests that access to carefully selected high-quality health information materials delivered digitally in the context of a community may result in improvements comparable to localized content in a hard-to-reach urban Hispanic population. Conclusions: Our study highlights the potential of making carefully selected digital information accessible to hard-to-reach communities.